(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kostina L. S., Likhosherst O. H. The problem of the nominal use of pedagogical technologies in the process of humanistic formation of the student’s personality. Pedagogical technologies, the use of which is performed on the basis of humanist approach to the university economics students’ personality formation, are considered in the article. The main problems of their nominal use in educational process are determined.